Book Review: Reading the Term Dalâl in The Qur’an - A.Baliyo Eko Prasetyo (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
Book : Kesesatan dalam Perspektif Al-Qur’anAuthor : Aibdi RahmatPublisher : Pustaka Pelajar, YogyakartaEdition : I, March 2007Content : viii + 228 pages